2022
DOI: 10.3390/su14105999
|View full text |Cite
|
Sign up to set email alerts
|

A Real-Time Comparison of Four Particulate Matter Size Fractions in the Personal Breathing Zone of Paris Subway Workers: A Six-Week Prospective Study

Abstract: We developed a Bayesian spline model for real-time mass concentrations of particulate matter (PM10, PM2.5, PM1, and PM0.3) measured simultaneously in the personal breathing zone of Parisian subway workers. The measurements were performed by GRIMM, a gravimetric method, and DiSCmini during the workers’ work shifts over two consecutive weeks. The measured PM concentrations were analyzed with respect to the working environment, the underground station, and any specific events that occurred during the work shift. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…The personal measurement campaigns included the 2016 Locomotive Operators, the 2017 Security Guards, and the 2019 Work Package 2 (2019 WP2) of the research project ROBoCoP (Respiratory Disease Occupational Biomonitoring Collaborative Project) [61]. The results of this campaign were published previously [36,37,62].…”
Section: Exposure Considered and Measurement Data Usedmentioning
confidence: 99%
See 3 more Smart Citations
“…The personal measurement campaigns included the 2016 Locomotive Operators, the 2017 Security Guards, and the 2019 Work Package 2 (2019 WP2) of the research project ROBoCoP (Respiratory Disease Occupational Biomonitoring Collaborative Project) [61]. The results of this campaign were published previously [36,37,62].…”
Section: Exposure Considered and Measurement Data Usedmentioning
confidence: 99%
“…The principle of JEM construction involves the definition of homogenous exposure groups (i.e., groups that combine workers with similar exposure level because of tasks or similar work conditions). From the previous studies, we identified that PM concentrations vary depending on the calendar period, line, and geographic sector of the subway network [15,36,57]. Therefore, adding these determinants as additional dimensions to define homogeneous exposure groups in the JEM was important.…”
Section: Jem Dimensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the presence of ultrafine particles (UFPs) in subway networks was pointed out as a concern, it seems suitable in the future to include UFP concentrations in our database as well. As for the time being, UFPs are not subject to any regulation, and their measurements in the Parisian subway are still exceptional [55][56][57]. Moreover, details on the chemical composition of PMs, especially their heavy metal content, which plays a role in the biological inflammation caused by these pollutants [24,25], would be important to assess in the future.…”
Section: Strengths and Limitations Of The Databasementioning
confidence: 99%